Efficacy and effectiveness of bulking agents in the treatment of stress and mixed urinary incontinence: A systematic review and meta-analysis. (March 2020) - Capobianco, Giampiero; Saderi, Laura; Dessole, Francesco; Petrillo, Marco; Dessole, Margherita; Piana, Andrea; Cherchi, Pier Luigi; Dessole, Salvatore; Sotgiu, Giovanni
Highlights: Urethral bulking agents are of proven efficacy/effectiveness in one in two patients with urinary incontinence. They are potentially a first-line surgical therapy for stress/mixed urinary incontinence. They could be recommended for patients with anaesthesia risk, elderly patients, or patients reluctant to undergo surgery. They should not be offered as first-line therapy for those women desiring a "one-time" durable solution. Abstract: The objective of this systematic review and meta-analysis was to evaluate the efficacy and the effectiveness, as well as the safety and tolerability, of urethral bulking agents (UBAs) in women with mixed or stress urinary incontinence. PubMed, Scopus, and the Cochrane Central Register of Controlled Trials were used to identify relevant articles. In total, 3510 records were found. A total of 42 full texts were evaluated but only 21 (48.8 %) were selected for the qualitative and quantitative analysis. The pooled improvement rate in studies with a follow-up of ≤1 and >1 year was 46.0 % (95 % CI: 37.0 %–57.0 %; I 2 : 88.9 %) and 57.0 % (95 % CI: 39.0 %–74.0 %; I 2 : 89.6 %), respectively. The outcome 'cure/dryness' ranged from 9.1 % to 56.7 %. The pooled cure rate was 26.0 % (95 % CI: 21.0 %–32.0 %; I 2 : 89.9 %) and 21.0 % (95 % CI: 16.0 %–27.0 %; I 2 : 34.2 %) in females with a follow-up of ≤1 and >1 year, respectively. The treatment success rate ranged from 32.7 % to 93.3 % in 12 studies; it was objectively assessed with different tools (e.g., the Stamey scale in 5 studies). The pooled objective treatment success rate was 7.0 % (95 % CI: 59.0.0 %-75.0 %; I 2 : 82.4 %) and 46.0 % (95 % CI: 37.0 %–55.0 %; I 2 : 55.3 %) in women with a follow-up of ≤12 and >12 months, respectively. The percentage of adverse events was 0.4 % (vaginal infection, irritation, lichen sclerosus, worsening urinary incontinence). However, the use of UBAs as the first-line therapy should be demonstrated in more comparative studies (randomized studies MUSs vs. UBAs). UBAs should be considered a first-line surgical therapy only for women with SUI and mixed UI with high anaesthesia risk, elderly patients, or patients reluctant to undergo surgery. Thus, UBAs should not be offered as first-line therapy for those women desiring a "one-time" durable solution for primary or recurrent SUI.